A method for preparing an ultra-low temperature sintered alumina ceramic

CN118955104BActive Publication Date: 2026-10-27YANTAI HEJING CERAMIC NEW MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411026669.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2026-10-27
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

然而由于氧化铝陶瓷烧结温度高,需要消耗大量的能源,对热工设备的要求也较高,因此在一定范围内限制了氧化铝陶瓷的使用范围;型陶瓷胶态成型工艺可以降低陶瓷的制造成本,提高陶瓷零部件的可靠性,因而受到广泛的关注

Benefits of technology

[0032]1、该一种超低温烧结的氧化铝陶瓷的制备方法中,采用B2O3-Li2O-Cr2O3-TiO2-SiO2助烧体系,其中,使B2O3作为强熔剂原料,使氧化铝能够在较低的温度下完成致密化过程,即所谓的超低温烧结,有助于加速物质迁移和颗粒重排,促进烧结体的致密化;且B2O3与SiO2形成的复杂含硼硅酸盐熔体能进一步溶解Al 2O3颗粒,激活氧化铝的烧结活性,有利于形成更加紧密的微观结构,从而提高陶瓷的机械强度和耐磨性;该助烧体系通过多种机制协同作用,有效降低了烧结温度,提高了烧结效率,同时优化了氧化铝陶瓷的微观结构和力学性能,解决了传统烧结方法中可能存在的强度、韧性不足等问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004968744430000101
    Figure BDA0004968744430000101
Patent Text Reader

Abstract

The present application relates to the technical field of alumina ceramic preparation, in particular to a preparation method of ultra-low temperature sintered alumina ceramic, comprising the following steps: S1.1, alumina powder and water are put into a ball mill equipped with ball stones in a ratio of 3-4:1 for ball milling for 20-30 hours to obtain alumina grinding slurry, and the specific gravity of the alumina grinding slurry is 1.60-1.70; S1.2, B2O3-Li2O-Cr2O3-TiO2-SiO2 is selected as a sintering aid system and mixed uniformly by a mixer; S1.3, 2-3wt% of cadralan glue is heated to be dissolved and then added to the prepared alumina slurry, and after stirring uniformly, the alumina ceramic mold is poured; S1.4, the baked alumina blank is put into a sintering kiln to form the alumina ceramic. Nano-modified silicon carbide is introduced into the mixed sintering aid system, and a firm interface structure is formed between the nano-modified silicon carbide and the alumina matrix, which can effectively prevent the initiation and expansion of cracks on the interface between the nano-modified silicon carbide particles and the alumina matrix, thereby improving the bending strength of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alumina ceramic preparation technology, and more specifically, to a method for preparing alumina ceramics by ultra-low temperature sintering. Background Technology

[0002] Alumina ceramics are among the most common advanced precision ceramic materials, and also relatively traditional. High-purity alumina ceramics, as an excellent ceramic material, have been widely used in many industries. This material exhibits superior performance in electrical insulation, high thermal conductivity, high chemical resistance, good wear resistance, and low thermal expansion. However, due to the high sintering temperature of alumina ceramics, it requires a large amount of energy and places high demands on thermal equipment, thus limiting its application range to a certain extent. Colloidal molding processes for ceramics can reduce manufacturing costs and improve the reliability of ceramic parts, and have therefore attracted widespread attention. Gel injection molding produces green bodies with high strength, near-net-shape dimensions, and can form large green bodies with complex properties, making it considered an advanced industrial molding method. However, the neurotoxicity of acrylamide monomers limits its widespread application. Therefore, selecting novel, non-toxic gel systems to achieve non-toxic gel injection molding of ceramics has significant practical implications.

[0003] To address the shortcomings of existing technologies, there is an urgent need for a method for preparing alumina ceramics by ultra-low temperature sintering, in order to prepare alumina ceramic blanks with complex shapes and improve the flexural strength, compressive strength, fracture toughness, and Young's modulus properties of alumina ceramics. Therefore, we propose a method for preparing alumina ceramics by ultra-low temperature sintering. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing alumina ceramics by ultra-low temperature sintering, so as to solve the problems mentioned in the background art, which are aimed at overcoming the shortcomings of the prior art and improving the flexural strength, compressive strength, fracture toughness and Young's modulus properties of alumina ceramics.

[0005] To achieve the above objectives, the present invention provides a method for preparing alumina ceramics sintered at ultra-low temperatures, comprising the following steps:

[0006] S1.1 Alumina powder and water are added to a ball mill containing ball stones at a ratio of 3 to 4:1 and ball milled for 20 to 30 hours to obtain alumina grinding slurry. The specific gravity of the alumina grinding slurry is 1.60 to 1.70, which indicates that a suitable solid-liquid ratio and particle fineness have been achieved.

[0007] The alumina grinding slurry, alumina powder, dispersant and adhesive are mixed evenly in a ratio of 200:100-180:30-50:2-5, and the specific gravity after mixing is 1.80-1.90.

[0008] S1.2 Select B2O3-Li2O-Cr2O3-TiO2-SiO2 as the calcination aid system, and mix B2O3, Li2O, Cr2O3, TiO2 and SiO2 evenly in a weight ratio of 3~4:0.5~1:0.5~1:1~2:0.5~1 using a mixer;

[0009] Nano-modified silicon carbide is introduced into the mixed sintering aid system, wherein the mass ratio of nano-modified silicon carbide to the sintering aid system is 1 to 3:100.

[0010] B2O3 is a strong fluxing agent that reacts with SiO2 to form a low-melting-point glass during firing, thus facilitating the sintering process. Furthermore, B2O3 readily reacts with SiO2 to form low-melting-point compounds, further dissolving Al2O3 and forming a more complex boron-containing silicate melt, activating the sintering of corundum and improving its mechanical strength and wear resistance. Due to Cr... 3+ With Al 3+ The two ions have similar radii and identical crystal forms, and readily form solid solutions with Al₂O₃; TiO₂ reacts with Al₂O₃ to form Al₂Ti₇O. 15 Solid-state sintering is more likely to promote the growth and densification of alumina ceramic grains; Li2O can form a liquid phase with Al2O3 during high-temperature processes, increasing the fluidity of the system;

[0011] S1.3. After heating 2-3 wt% of cardlan gum to dissolve it, add it to the prepared alumina slurry, stir evenly, and then pour it into the mold of the alumina ceramic. Place it in a curing room at 20-30℃ and wait for the slurry to cool before demolding. Cardlan gum is used to increase the viscosity of the alumina slurry, which helps to improve the stability of the molded body, reduce cracking, and maintain the integrity of the shape during subsequent drying and sintering.

[0012] After demolding, the alumina blanks are cured in the curing room for 12-24 hours, and then transferred to the drying room at 80-85℃ for 10-16 hours.

[0013] S1.4. After baking, the alumina blank is placed in a sintering kiln and sintered at 1350℃-1400℃ for 24-28 hours to form alumina ceramic.

[0014] Preferably, in S1.1, the alumina powder is a mixed powder with a mass ratio of 100-200:300-400 mesh of 2:1.

[0015] Preferably, in step S1.1, the dispersant is one or a mixture of multiple types of ammonium citrate, polycarboxylate, and polyacrylate.

[0016] Preferably, in step S1.1, the adhesive is one or a mixture of polyvinyl alcohol, polyacrylamide, and polyethylene glycol.

[0017] Preferably, in step S1.1, the pH of the prepared alumina slurry is 9-10.

[0018] Preferably, in S1.2, the nano-modified silicon carbide is obtained by surface modification of nano-silicon carbide with γ-mercaptopropyltriethoxysilane;

[0019] Among them, γ-mercaptopropyltriethoxysilane is an organic compound containing a silane coupling agent. One end of γ-mercaptopropyltriethoxysilane contains a silane group that can react with the surface of inorganic materials (such as SiC), and the other end contains an organic functional group (thiol group), which can react with or be compatible with organic matrices (such as polymers). The silane group can react with the hydroxyl groups on the SiC surface to form stable siloxane bonds, thereby allowing the silane to adhere firmly to the SiC surface. The thiol group can react with or at least be compatible with functional groups in certain polymer matrices, thereby improving the interfacial bonding strength between SiC and the matrix.

[0020] Furthermore, nano-modified silicon carbide has extremely high strength and hardness. When it is uniformly distributed in the alumina matrix, it can effectively hinder the propagation of cracks and improve the bending strength and compressive strength of the material. This "bridging effect" and "pinning effect" can significantly improve the overall mechanical properties of the material.

[0021] Meanwhile, the strong interfacial bonding between nano-modified silicon carbide and alumina matrix can form a robust interfacial structure, further enhancing the overall performance of the composite material. By controlling the sintering conditions, the good bonding between nano-modified silicon carbide and alumina can be promoted, thereby enhancing interfacial compatibility.

[0022] The specific modification steps are as follows:

[0023] S2.1 Disperse nano-silicon carbide powder in ethanol solvent to obtain a 20wt% nano-silicon carbide solution, and add γ-mercaptopropyltriethoxysilane to the nano-silicon carbide solution;

[0024] S2.2 At room temperature, the mixture is stirred with a stirrer to promote the chemical reaction between γ-mercaptopropyltriethoxysilane and the hydroxyl groups on the surface of nano-silicon carbide, forming stable chemical bonds.

[0025] The mercapto (-SH) and / or silanol (-Si(OC2H5)3) in γ-mercaptopropyltriethoxysilane undergo condensation or substitution reactions with the hydroxyl (-OH) on the surface of SiC to form stable siloxane bonds (-SiiOSi-) or thiol bonds, thereby achieving surface coating and modification of nano-silicon carbide.

[0026] S2.3 After the reaction is complete, unreacted γ-mercaptopropyltriethoxysilane and other byproducts are removed by filtration;

[0027] S2.4. The modified nano-silicon carbide powder is dried at a suitable temperature to obtain the final product.

[0028] Preferably, in step S2.1, the mass ratio of γ-mercaptopropyltriethoxysilane to nano-silicon carbide powder is 1:10.

[0029] Preferably, in step S2.2, the stirrer continuously stirs at a speed of 680-800 rpm for 6-8 hours.

[0030] Preferably, in S1.4, the sintering kiln is a shuttle kiln.

[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0032] 1. In this method for preparing alumina ceramics by ultra-low temperature sintering, a B2O3-Li2O-Cr2O3-TiO2-SiO2 sintering aid system is adopted. B2O3 acts as a strong flux, enabling alumina to complete the densification process at a lower temperature, i.e., ultra-low temperature sintering. This helps accelerate material migration and particle rearrangement, promoting densification of the sintered body. Furthermore, the complex borosilicate melt formed by B2O3 and SiO2 can further dissolve Al2O3 particles, activating the sintering activity of alumina and facilitating the formation of a denser microstructure, thereby improving the mechanical strength and wear resistance of the ceramic. This sintering aid system, through the synergistic effect of multiple mechanisms, effectively reduces the sintering temperature, improves sintering efficiency, and optimizes the microstructure and mechanical properties of alumina ceramics, solving problems such as insufficient strength and toughness that may exist in traditional sintering methods.

[0033] 2. In the preparation method of ultra-low temperature sintered alumina ceramic, nano-modified silicon carbide is introduced into the mixed sintering aid system. The interfacial bonding force between nano-modified silicon carbide and alumina matrix is ​​strong, which can form a solid interfacial structure and further improve the overall performance of the composite material. By controlling the sintering conditions, the good bonding between nano-modified silicon carbide and alumina is promoted, and the interfacial compatibility is enhanced. The enhanced interfacial bonding force can effectively prevent the initiation and propagation of cracks at the interface between nano-modified silicon carbide particles and alumina matrix. Under bending load, the stronger interface can more effectively transfer stress and avoid stress concentration, thereby improving the bending strength of the composite material. Detailed Implementation

[0034] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0035] This invention relates to a method for preparing alumina ceramics sintered at ultra-low temperatures, wherein the dispersant is one or a mixture of ammonium citrate, polycarboxylate, and polyacrylate; and the adhesive is one or a mixture of polyvinyl alcohol, polyacrylamide, and polyethylene glycol.

[0036] In this embodiment, ammonium citrate is preferably used as the dispersant, and polyvinyl alcohol is preferably used as the adhesive.

[0037] B2O3 is a strong fluxing agent that reacts with SiO2 to form a low-melting-point glass during firing, thus facilitating the sintering process. Furthermore, B2O3 readily reacts with SiO2 to form low-melting-point compounds, further dissolving Al2O3 and forming a more complex boron-containing silicate melt, activating the sintering of corundum and improving its mechanical strength and wear resistance. Due to Cr... 3+ With Al 3+ The two ions have similar radii and identical crystal forms, and readily form solid solutions with Al₂O₃; TiO₂ reacts with Al₂O₃ to form Al₂Ti₇O. 15 Solid-state sintering is more likely to promote the growth and densification of alumina ceramic grains; Li2O can form a liquid phase with Al2O3 during high-temperature processes, increasing the fluidity of the system;

[0038] Among them, γ-mercaptopropyltriethoxysilane is an organic compound containing a silane coupling agent. One end of γ-mercaptopropyltriethoxysilane contains a silane group that can react with the surface of inorganic materials (such as SiC), and the other end contains an organic functional group (thiol group), which can react with or be compatible with organic matrices (such as polymers). The silane group can react with the hydroxyl groups on the SiC surface to form stable siloxane bonds, thereby allowing the silane to adhere firmly to the SiC surface. The thiol group can react with or at least be compatible with functional groups in certain polymer matrices, thereby improving the interfacial bonding strength between SiC and the matrix.

[0039] Furthermore, nano-modified silicon carbide has extremely high strength and hardness. When it is uniformly distributed in the alumina matrix, it can effectively hinder the propagation of cracks and improve the bending strength and compressive strength of the material. This "bridging effect" and "pinning effect" can significantly improve the overall mechanical properties of the material.

[0040] Meanwhile, the strong interfacial bonding between nano-modified silicon carbide and alumina matrix can form a robust interfacial structure, further enhancing the overall performance of the composite material. By controlling the sintering conditions, the good bonding between nano-modified silicon carbide and alumina can be promoted, thereby enhancing interfacial compatibility.

[0041] The modification steps for nano-modified silicon carbide are as follows:

[0042] S2.1 Disperse the nano silicon carbide powder in ethanol solvent to obtain a 20wt% nano silicon carbide solution. Add γ-mercaptopropyltriethoxysilane to the nano silicon carbide solution. The mass ratio of γ-mercaptopropyltriethoxysilane to nano silicon carbide powder is 1:10.

[0043] S2.2 At room temperature, use a stirrer to continuously stir at a speed of 680-800 rpm for 6-8 hours to promote the chemical reaction between γ-mercaptopropyltriethoxysilane and the hydroxyl groups on the surface of nano-silicon carbide to form stable chemical bonds.

[0044] The mercapto (-SH) and / or silanol (-Si(OC2H5)3) in γ-mercaptopropyltriethoxysilane undergo condensation or substitution reactions with the hydroxyl (-OH) on the surface of SiC to form stable siloxane bonds (-SiiOSi-) or thiol bonds, thereby achieving surface coating and modification of nano-silicon carbide.

[0045] S2.3 After the reaction is complete, unreacted γ-mercaptopropyltriethoxysilane and other byproducts are removed by filtration;

[0046] S2.4. The modified nano-silicon carbide powder is dried at a suitable temperature to obtain the final product.

[0047] Example 1

[0048] The preparation method of ultra-low temperature sintered alumina ceramic is as follows:

[0049] S1.1 Alumina powder and water are added to a ball mill containing ball stones at a ratio of 3:1 and ball milled for 20 hours to obtain alumina grinding slurry. The specific gravity of the alumina grinding slurry is 1.63 and the pH of the prepared alumina slurry is 9.4.

[0050] Alumina grinding slurry, alumina powder, polycarboxylate dispersant and polyacrylamide adhesive are mixed evenly in a ratio of 200:160:35:3. The specific gravity after mixing is 1.82, and the alumina powder is a mixed powder with a mass ratio of 100-200:300-400 mesh of 2:1.

[0051] S1.2 Select B2O3-Li2O-Cr2O3-TiO2-SiO2 as the calcination aid system, and mix B2O3, Li2O, Cr2O3, TiO2 and SiO2 evenly in a weight ratio of 3:1:0.5:1:1 using a mixer;

[0052] Nano-modified silicon carbide was introduced into the mixed sintering aid system. The nano-modified silicon carbide was obtained by surface modification of nano-silicon carbide with γ-mercaptopropyltriethoxysilane. The mass ratio of nano-modified silicon carbide to sintering aid system was 1:100.

[0053] S1.3. After heating 3wt% of cardlan gum to dissolve it, add it to the prepared alumina slurry, stir evenly, pour it into the mold of alumina ceramic, place it in a curing room at 30℃, and start demolding after the slurry cools down.

[0054] After demolding, the alumina blanks are cured in the curing room for 12 hours, and then transferred to the drying room at 80°C for 10 hours.

[0055] S1.4. After the alumina blanks are baked, they are sintered in a shuttle kiln at 138°C for 24 hours to form alumina ceramics.

[0056] Example 2

[0057] The preparation method of ultra-low temperature sintered alumina ceramic is as follows:

[0058] S1.1 Alumina powder and water are added to a ball mill containing ball stones at a ratio of 3:1 and ball milled for 20 hours to obtain alumina grinding slurry. The specific gravity of the alumina grinding slurry is 1.63 and the pH of the prepared alumina slurry is 9.4.

[0059] Alumina grinding slurry, alumina powder, polycarboxylate dispersant and polyacrylamide adhesive are mixed evenly in a ratio of 200:160:35:3. The specific gravity after mixing is 1.82, and the alumina powder is a mixed powder with a mass ratio of 100-200:300-400 mesh of 2:1.

[0060] S1.2 Select B2O3-Li2O-Cr2O3-TiO2-SiO2 as the calcination aid system, and mix B2O3, Li2O, Cr2O3, TiO2 and SiO2 evenly in a weight ratio of 3:1:0.5:1:1 using a mixer;

[0061] Nano-modified silicon carbide was introduced into the mixed calcination aid system. The nano-modified silicon carbide was obtained by surface modification of nano-silicon carbide with γ-mercaptopropyltriethoxysilane. The mass ratio of nano-modified silicon carbide to the calcination aid system was 3:100.

[0062] S1.3. After heating 3wt% of cardlan gum to dissolve it, add it to the prepared alumina slurry, stir evenly, pour it into the mold of alumina ceramic, place it in a curing room at 30℃, and start demolding after the slurry cools down.

[0063] After demolding, the alumina blanks are cured in the curing room for 12 hours, and then transferred to the drying room at 80°C for 10 hours.

[0064] S1.4. After the alumina blanks are baked, they are sintered in a shuttle kiln at 138°C for 24 hours to form alumina ceramics.

[0065] Example 3

[0066] The preparation method of ultra-low temperature sintered alumina ceramic is as follows:

[0067] S1.1 Alumina powder and water are added to a ball mill containing ball stones at a ratio of 3:1 and ball milled for 20 to 30 hours to obtain alumina grinding slurry. The specific gravity of the alumina grinding slurry is 1.68 and the pH of the prepared alumina slurry is 9.6.

[0068] Alumina grinding slurry, alumina powder, ammonium citrate dispersant and polyvinyl alcohol adhesive are mixed evenly in a ratio of 200:130:40:3. The specific gravity after mixing is 1.87, and the alumina powder is a mixed powder with a mass ratio of 100-200:300-400 mesh of 2:1.

[0069] S1.2 Select B2O3-Li2O-Cr2O3-TiO2-SiO2 as the calcination aid system, and mix B2O3, Li2O, Cr2O3, TiO2 and SiO2 evenly in a weight ratio of 4:0.5:1:2:0.5 using a mixer;

[0070] Nano-modified silicon carbide was introduced into the mixed calcination aid system. The nano-modified silicon carbide was obtained by surface modification of nano-silicon carbide with γ-mercaptopropyltriethoxysilane. The mass ratio of nano-modified silicon carbide to the calcination aid system was 3:100.

[0071] S1.3. After heating 3wt% of cardlan gum to dissolve it, add it to the prepared alumina slurry, stir evenly, pour it into the mold of alumina ceramic, place it in a curing room at 25℃, and start demolding after the slurry cools down.

[0072] After demolding, the alumina blanks are cured in the curing room for 24 hours, and then transferred to the drying room at 85℃ for 12 hours.

[0073] S1.4. The baked alumina blanks are placed in a shuttle kiln and sintered at 1400℃ for 24 hours to form alumina ceramics.

[0074] Comparative Example 1

[0075] Using the method of Example 2, no nano-modified silicon carbide was introduced into the mixed calcination aid system.

[0076] Comparative Example 1

[0077] Using the method of Example 2, the nano-silicon carbide in the mixed calcination aid system was not modified by γ-mercaptopropyltriethoxysilane.

[0078] The performance testing methods for the ultra-low temperature sintered alumina ceramics prepared in Examples 1-3 and Comparative Examples 1-2 are as follows:

[0079] Referring to GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics", the corresponding testing equipment, specimens, test procedures, result calculation and data processing methods are specified. The three-point bending or four-point bending method is adopted and carried out on a material mechanics testing machine. The bending strength is determined by measuring the maximum load of the specimen at bending failure.

[0080] Referring to B / T 4740-1999 "Test Method for Compressive Strength of Ceramic Materials", the test equipment, sample preparation, test procedure, and result calculation are specified. The unconfined compression test method is adopted. On the pressure testing machine, pressure is applied at a certain speed until the sample is broken, and the maximum pressure value at the time of failure is recorded.

[0081] Referring to GB / T 23806-2009 "Test Method for Fracture Toughness of Fine Ceramics - Single-sided Precracked Beam Method", the corresponding test methods and requirements are specified. The surface crack bending method is used to evaluate the fracture toughness of the material by measuring the crack propagation behavior of the specimen under external load.

[0082] Referring to GB / T 10700-2006 "Test Method for Elastic Modulus of Fine Ceramics - Bending Method", the corresponding test methods and requirements are specified. The Young's modulus is determined by measuring the natural frequency of the material using the resonance method.

[0083] Referring to the national standard GB / T 3810.9-2016 on the testing of thermal shock resistance of ceramic tiles, this paper tests the thermal shock resistance of alumina ceramics, focusing on the standards involved in the determination of thermal shock resistance of ceramic tiles.

[0084] The mechanical properties of alumina ceramics are summarized in Table 1.

[0085] Table 1. Mechanical property data of alumina ceramics in Examples 1-3 and Comparative Example 1

[0086]

[0087] The above data clearly demonstrates the difference between Examples 1-3 and Comparative Examples 1-2, as detailed below:

[0088] As can be seen from Examples 1-3, as the proportion of nano-modified silicon carbide introduced into the sintering aid system increases, the mechanical properties of alumina ceramics are significantly improved, especially the flexural strength, compressive strength, fracture toughness and Young's modulus of the ceramics.

[0089] Nano-modified silicon carbide has extremely high strength and hardness. When it is uniformly distributed in the alumina matrix, it can effectively hinder the propagation of cracks and improve the bending strength and compressive strength of the material. This "bridging effect" and "pinning effect" can significantly improve the overall mechanical properties of the material.

[0090] Taking all factors into consideration, Example 2 is selected as the optimal example. A comparison between Example 2 and Comparative Example 1 shows that:

[0091] Without the introduction of nano-modified silicon carbide into the mixed sintering system, the mechanical properties of alumina ceramics, especially the flexural strength, compressive strength, fracture toughness and Young's modulus, were significantly reduced. This indicates that nano-modified silicon carbide has a significant impact on improving the flexural strength, compressive strength and fracture toughness of alumina ceramics.

[0092] γ-Mercaptopropyltriethoxysilane is an organic compound containing a silane coupling agent. One end of γ-mercaptopropyltriethoxysilane contains a silane group that can react with the surface of inorganic materials (such as SiC), while the other end contains an organic functional group (thiol group), which can react with or be compatible with organic matrices (such as polymers). The silane group can react with the hydroxyl groups on the SiC surface to form stable siloxane bonds, thus allowing the silane to adhere firmly to the SiC surface. The thiol group can react with or at least be compatible with functional groups in certain polymer matrices, thereby increasing the interfacial bonding strength between SiC and the matrix, reducing interfacial voids, increasing effective load transfer, and further improving the mechanical properties of the composite material. The modification effect of γ-mercaptopropyltriethoxysilane helps control the dispersion of nanoparticles and reduce agglomeration, thereby optimizing the microstructure of the material and enhancing its toughness and overall stability.

[0093] Furthermore, by combining Example 2 and Comparative Example 1 with Comparative Example 2, it can be seen that:

[0094] When the nano-silicon carbide in the mixed sintering aid system was not modified by γ-mercaptopropyltriethoxysilane and was directly mixed with the sintering aid system, the mechanical properties of alumina ceramics, especially the flexural strength, compressive strength, fracture toughness and Young's modulus, were significantly reduced. However, compared with Comparative Example 1, the mechanical properties of alumina ceramics in Comparative Example 2 were improved. This shows that nano-silicon carbide has a significant effect on improving the flexural strength, compressive strength, fracture toughness and Young's modulus of alumina ceramics, and γ-mercaptopropyltriethoxysilane can significantly improve the flexural strength, compressive strength and fracture toughness of alumina ceramics.

[0095] In summary, the strong interfacial bonding between nano-modified silicon carbide and the alumina matrix forms a robust interfacial structure, further enhancing the overall performance of the composite material. By controlling the sintering conditions, a good bond between nano-modified silicon carbide and alumina is promoted, strengthening interfacial compatibility. The enhanced interfacial bonding effectively prevents the initiation and propagation of cracks at the interface between nano-modified silicon carbide particles and the alumina matrix. Under bending loads, a stronger interface can more effectively transfer stress, avoiding stress concentration and thus improving the flexural strength of the composite material. As a reinforcing phase, the high strength and hardness of nano-modified silicon carbide significantly improve the composite material's resistance to compressive loads. The good interfacial bonding ensures that the reinforcing phase does not detach under high pressure, maintaining the overall stability and strength of the material and improving its compressive strength.

[0096] Meanwhile, the addition of nano-modified silicon carbide and interface optimization help to alter the crack propagation path. When microcracks exist in the material, a robust interface can cause cracks to deflect or bypass reinforcing particles, increasing the resistance to crack propagation and thus absorbing more energy, which directly leads to an improvement in the fracture toughness of the material. In addition, the bridging effect and crack pinning effect of nanoparticles are also important mechanisms for improving fracture toughness.

[0097] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing ultra-low temperature sintered alumina ceramics, characterized in that, Includes the following steps: S1.1 Alumina powder and water are added to a ball mill containing ball stones at a ratio of 3 to 4:1 and ball milled for 20 to 30 hours to obtain alumina grinding slurry with a specific gravity of 1.60 to 1.

70. The alumina grinding slurry, alumina powder, dispersant and adhesive are mixed evenly in a ratio of 200:100-180:30-50:2-5, and the specific gravity after mixing is 1.80-1.

90. S1.2 Select B2O3-Li2O-Cr2O3-TiO2-SiO2 as the calcination aid system, and mix B2O3, Li2O, Cr2O3, TiO2 and SiO2 evenly in a weight ratio of 3~4:0.5~1:0.5~1:1~2:0.5~1 using a mixer; Nano-modified silicon carbide is introduced into the mixed sintering aid system, wherein the mass ratio of nano-modified silicon carbide to the sintering aid system is 1 to 3:

100. In step S1.2, the nano-modified silicon carbide is obtained by surface modification of nano-silicon carbide with γ-mercaptopropyltriethoxysilane; The specific modification steps are as follows: S2.1 Disperse nano-silicon carbide powder in ethanol solvent to obtain a 20wt% nano-silicon carbide solution, and add γ-mercaptopropyltriethoxysilane to the nano-silicon carbide solution; S2.2 At room temperature, stir with a stirrer to promote the chemical reaction between γ-mercaptopropyltriethoxysilane and the hydroxyl groups on the surface of nano-silicon carbide; S2.3 After the reaction is complete, unreacted γ-mercaptopropyltriethoxysilane and other byproducts are removed by filtration; S2.

4. The modified nano-silicon carbide powder is dried at a suitable temperature to obtain the final product; S1.

3. Heat 2-3wt% of cardlan gum to dissolve it, then add it to the prepared alumina slurry. Stir evenly and pour it into the mold of alumina ceramic. Place it in a curing room at 20-30℃. After the slurry cools, start demolding. After demolding, the alumina blanks are cured in the curing room for 12-24 hours, and then transferred to the drying room at 80-85℃ for 10-16 hours. S1.

4. After baking, the alumina blank is placed in a sintering kiln and sintered at 1350℃-1400℃ for 24-28 hours to form alumina ceramic.

2. The method for preparing ultra-low temperature sintered alumina ceramics according to claim 1, characterized in that, In S1.1, the alumina powder is a mixed powder with a mass ratio of 100-200:300-400 mesh of 2:

1.

3. The method for preparing ultra-low temperature sintered alumina ceramics according to claim 1, characterized in that, In S1.1, the dispersant is one or a mixture of multiple types of ammonium citrate, polycarboxylate, and polyacrylate.

4. The method for preparing ultra-low temperature sintered alumina ceramics according to claim 1, characterized in that, In S1.1, the adhesive is one or a mixture of polyvinyl alcohol, polyacrylamide and polyethylene glycol.

5. The method for preparing ultra-low temperature sintered alumina ceramics according to claim 1, characterized in that, In step S1.1, the pH of the prepared alumina slurry is 9-10.

6. The method for preparing ultra-low temperature sintered alumina ceramics according to claim 1, characterized in that, In S2.1, the mass ratio of γ-mercaptopropyltriethoxysilane to nano-silicon carbide powder is 1:

10.

7. The method for preparing ultra-low temperature sintered alumina ceramics according to claim 1, characterized in that, In step S2.2, the stirrer continuously stirs at a speed of 680-800 rpm for 6-8 hours.

8. The method for preparing ultra-low temperature sintered alumina ceramics according to claim 1, characterized in that, In S1.4, a shuttle kiln is selected as the sintering kiln.

Citation Information

Patent Citations

  • Silicon carbide whisker reinforced alumina ceramic composites

    US5108963A